Perkembangan, Tantangan, Dan Peluang Bank Syariah - M. Zainuddin Alanshori (Universitas Islam Lamongan, 2016)
Financial institutions have not been known clearly in the history of Islam. But the principles of exchange and borrowing occur at the time of the Prophet, even earlier. It is undeniable that progress of economic development and trade has influenced the birth of institutions that play a role in financial traffic. History and development of finance and financial institutions from time to time is rapidly increasing, many changes and improvements from various sides. Both of the systems used, development of institution role and other. History has recorded it, ranging from ancient economic experts later developed further by his followers until the economic experts in modern times. Individuals have been carrying out banking functions at the time of the Prophet Muhammad even though these individuals did not conduct all banking functions. There is prophet’s friends who carry out the function of receiving deposits treasure, there are companions who carry out the functions of money borrowing, there is who performing the function of remittances, and some are providing working capital. Islamic banks are affected by five factors, both internal and external. The fifth factor is management, owner, customers, public, competitor, regulator, supervisor, and infrastructure. Manager and owner are required to have integrity and competence, adherence to Islamic principles, and compliance with precautionary principle. Customer or community with integrity, competence, and loyalty. Competitors or substitution consist of conventional banks and other financial institutions. Regulator, supervisor, and other bodies consist of BI, Licensing, Regulation and Supervision, National Shariah Board (DSN); fatwa on business activities from Shariah Supervisor Board (DPS), IAI, IAS, PAPSI, Audit Guidelines, the Arbitration Board and others, and infrastructure that consists of macro-economic conditions, the real , monetary , fiscal and foreign sector. Keywords: Development of Islamic bank, Challenge, Opportunity